The treatment of ongoing contracts in the law of distressed businesses - EL KODMIRI , Afafe; BELAMIN, Samir (Revue Internationale du Chercheur, 2025)
Abstract This study analyzes the legal regime of ongoing contracts established by Moroccan Law 15-95 relating to the prevention and treatment of business difficulties. It examines the sought-after balance between the imperative of safeguarding the company and protecting contractors' rights. The analysis reveals that the legislator has implemented a sophisticated system governing both the substantive conditions and procedural modalities for maintaining ongoing contracts. The trustee is given a central role, with extraordinary but strictly regulated prerogatives. In return, contractors benefit from significant legal guarantees and a contractual non-performance treatment system adapted to collective proceedings' challenges. While this regime demonstrates a search for balance between the interests at stake, improvements remain desirable, particularly regarding deadlines, financial guarantees, and adaptation to new contractual forms. The future effectiveness of the system will depend on its ability to integrate technological and economic developments while preserving its primary purpose: reconciling company recovery with contractor protection.